Near‐infrared multispectral endoscopic imaging of deep artificial interproximal lesions in extracted teeth. Issue 5 (27th February 2019) - Zhou, Yaxuan; Lee, Robert C.; Finkleman, Sara; Sadr, Alizera; Seibel, Eric J.
Abstract : Background and Objective: A safer alternative method to radiographic imaging is needed. We present a multispectral near‐infrared scanning fiber endoscope (nirSFE) for dental imaging which is designed to be the smallest imaging probe with near‐infrared (NIR) imaging (1200–2000 nm). Materials and Methods: The prototype nirSFE is designed for wide‐field forward viewing of scanned laser illumination at 1310, 1460, or 1550 nm. Artificial lesions with varying sizes and locations were prepared on proximal surfaces of extracted human teeth to examine capability and limitation of this new dental imaging modality. Nineteen artificial interproximal lesions and several natural occlusal lesions on extracted teeth were imaged with nirSFE, OCT, and microCT. Results: Our nirSFE system has a flexible shaft as well as a probe tip with diameter of 1.6 mm and a rigid length of 9 mm. The small form factor and multispectral NIR imaging capability enables multiple viewing angles and reliable detection of lesions that can extend into the dentin. Among nineteen artificial interproximal lesions, the nirSFE reflectance imaging operating at 1460‐nm and OCT operating at 1310‐nm scanned illumination exhibited high sensitivity for interproximal lesions that were closer to occlusal surface. Diagnosis from a non‐blinded trained user by looking at real‐time occlusal‐side nirSFE videos indicate true positive rate of 78.9%. There were no false positives. Conclusions: This study demonstrates that nirSFE may be used for detecting occlusal lesions and interproximal lesions located less than 4 mm under the occlusal surface. Major advantages of this imaging system include multiple viewing angles due to flexibility and small form factor, as well as the ability to capture real‐time video. The multispectral nirSFE has the potential to be employed as a low‐cost dental camera for detecting dental lesions without exposure to ionizing radiation. Lasers Surg. Med. 51:459–465, 2019. © 2019 Wiley Periodicals, Inc.